The pathogenicity and immunogenicity of Pasteurella multocida in low and rich iron media - Hosseini, E; Tahamtan, Y; Molaee, H (Journal of the Hellenic Veterinary Medical Society, 2023)
Pasteurella multocida has the highest prevalence among animal populations and may cause hemorrhagic septicemia in cattle and pneumonia in sheep and goats. It has known that the pathogenicity of this organism depends on the levels of iron. Present study attempts to evaluate any changes in blood parameters and visceral organs of mice by cultivation of P.multocida under iron sufficient and insufficient conditions. P.multocida was cultured on three media: BHI alone, supplemented with bipyridyl and iron. They injected into the mice by intra-peritoneal rout. At the same time inactivated antigens were prepared from all medium and mice were immunized two weeks apart and blood samples were collected until weeks 9. Visceral organs were collected from dead mice for pathological studies. In contrast to immunogenicity and antibody titers, there are significant differences in pathogenicity and blood parameters in rich and limit iron condition.